Talian bekalan elektrik dan kesannya ke atas masyarakat dan nilai harta tanah - Mohd. Ghazalli, Kalthum (2007)
Transmission lines are the medium of transporting electricity to the society. Physically, they are prominent structures that dominate the skyline in the numerous areas where they exist in Malaysia. According to Tenaga Nasional Berhad (TNB), transmission line in Malaysia total 14,000 km in length. The length is expected to increase in line with the rise in demand for electricity in the whole country. Many researches done overseas has discovered that members of society living in proximity to transmission lines find them visually ugly, produce an unpleasant humming sound, cause interference in the media and communication equipments, leave a fear of possible electrocution and pose a potential health risk in the form of a multitude of cancer related diseases. A few researchers noted that these negative effects have caused properties in proximity to transmission lines to fall in value. This research seeks to discover the impact of transmission line on the society living in its vicinity and if it is a factor affecting value. Data is collected through a survey using questionnaires covering three different groups. They are people living in proximity to transmission lines in five selected different locations in Selangor, developers with experience developing a property affected by a transmission line and registered valuers. The survey uses the ‘guided face to face’ interview and interview by telephone methods. Data is analysed using the Frequency Analysis Technique and the Average Index Technique. The data analysed is presented in the pie charts, tables, histograms and others. The main findings of this research is that society living in proximity to transmission lines is aware of all the interferences and potential health risks, but is of the opinion that it is not a factor affecting the value of properties in proximity to it